STRENGHTENING AND DEVELOPING LOCAL LANGUAGE LITERATION THROUGH LOCAL CONTENT CURRICULUM OF PRIMARY SCHOOL: SYSTEMIC- FUNCTIONAL LINGUISTIC PERSPECTIVE - Putu Sutama; Maria Arina Luardini; Natalina Asi (Postgraduate School, Universitas Nusa Cendana, 2019)
Local language, which is maintained and respected by its speakers, is protected by the government as local language is a part of Indonesian culture stated in the national constitutions of UUD 1945, the TAP MPR No. II/MPR/1988, the National Language Politic and Policy of National Language, and constitution No. 24 dated in 2009 about languages. The Implementation of those regulations is written on Formal Education Curriculum that is in local content curriculum. One of the local content curriculum aspects is the lesson plan which consists of material component: texts or handouts, especially for primary school students. The opportunity for strengthening and developing the local language on Curriculum 2013 is integrated within the material of art and culture. Referring to the percentage of hours for learning local language in Art-Culture, it lack of time for local language materials. Consequently, the local language materials should be developed and strengthened, so the coming up generation of local language speakers will have optimal vocabulary for maintaining and developing mother tongue. This problem is discussed by applying Systemic-Functional Linguistics.